2005
DOI: 10.5144/0256-4947.2005.215
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of proteinuria with urinary protein to osmolality ratios in children with and without renal insufficiency

Abstract: BACKGROUNDSpot urine is recommended as an accurate method to determine proteinuria in children and adults. However, urinary excretion of creatinine may vary in newborns and spot urine may be influenced by the hydration-dehydration condition of patients. The study was done to assess the validity of the urine protein to osmolality ratio versus the urine protein to creatinine ratio in health and disease conditions.METHODSWe studied the correlation of the urine protein-osmolality ratio (Uprot/Uosm) and the urine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…There was no difference between SUPCR and SUPOR in predicting 24 HUP at this level. This is similar to the findings reported by two studies with slightly higher AUROC [19,20]. This is in keeping with some earlier studies [19,20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was no difference between SUPCR and SUPOR in predicting 24 HUP at this level. This is similar to the findings reported by two studies with slightly higher AUROC [19,20]. This is in keeping with some earlier studies [19,20].…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the findings reported by two studies with slightly higher AUROC [19,20]. This is in keeping with some earlier studies [19,20]. However SUPCR was found to be better than SUPOR when compared with 24 HUP in another study [21].…”
Section: Discussionsupporting
confidence: 92%
“…The cut-off value of protein-osmolality ratio to diagnose abnormal proteinuria was 0.38 mg/L: mOsmoles/kgH 2 O. This figure is close to the values reported by Kim et al and Hooman et al who used the turbidimetric method for measuring urinary protein (0.23 and 0.27 mg/L: mOsmoles/kgH 2 O respectively) 7,8 . Cut-off value to detect abnormal urinary protein excretion obtained in our study is higher than the value obtained by Morgenstern et al (0.15 mg/L: mOsmoles/kgH 2 O) where urine protein was measured by the pyrogallol red method, as in our study 4 .…”
Section: Discussionsupporting
confidence: 87%
“…In the study by Morgenstern et al the results in the paediatric population differed from the adult population, in that both protein-osmolality and protein-creatinine ratios were equally predictive of abnormal proteinuria in adults 4 . Hooman et al reported that according to ROC curves there is no difference between these two ratios in detecting either abnormal proteinuria or nephrotic proteinuria 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation